Analysis of the Motivations and Satisfaction towards Ecotourism in a National Recreation Area: The Samanes Park in Guayaquil, Ecuador - CARVACHE - FRANCO, Mauricio; CARVACHE - FRANCO, Wilmer; ARCE -BASTIDAS, Rafael; PROAÑO MOREIRA, José Luis (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018, 2018)
Studying the motivations and satisfaction of visitors in protected areas is increasingly important for the interaction with nature. The Samanes Park recreation area located in the city of Guayaquil in Ecuador is visited by national and international tourists for outdoor activities and for the purpose of being in contact with nature. The present empirical study was carried out in situ, for which univariate and bivariate techniques were applied using a questionnaire. The results show that the main motivations of the visit are "to enjoy its environment and pure air", "to enjoy its public recreation spaces", "to perform sports" and "to carry out activities in nature", which indicates the importance of ecotourism in this destination. The most valued attributes in satisfaction are "security", followed by "places of recreation". Visitors to the Samanes Park find general satisfaction in their visit and the vast majority are totally satisfied. All these findings show the importance of this site for ecotourism in Ecuador.